Understanding trends and drivers of malnutrition at subnational level: A crosscountry analysis in 15 Sub-Saharan African (SSA) countries - Kayitakire, Francois; Perez Hoyos, Ana; Custodio, Estefania; Nkunzimana, Tharcisse (2016)
Going the Last Mile: Accelerating Progress in Food Security and Nutrition workshop (June 14, 2016)